ALLERGEN-SPECIFIC MARKERS OF NASAL SECRET IN CHILDREN WITH COMBINED FORMS OF RESPIRATORY ALLERGOSIS (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
The paper presents the results of a study of allergen-specific markers in nasal secretions of children with combined forms of respiratory allergosis, including allergic rhinitis and bronchial asthma. A comprehensive analysis of the content of specific IgE, Th2-type cytokines (IL-4, IL-5, IL-13) in nasal secretions was performed in comparison with the indicators of the control group. A significant increase in the concentrations of these markers was found in patients with combined allergies, which reflects the high activity of local eosinophilic inflammation. The identified correlations between the levels of nasal specific IgE and IL-5 and the severity of clinical symptoms confirm the diagnostic and prognostic significance of these indicators.